PENGARUH PROMOSI JABATAN DAN KUALITAS TERHADAP MOTIVASI PEMERINTAH KOTA BEKASI - Syarief, Faroman; Utomo, Kurniawan Prambudi; Winardi, Muhammad Aziz; Kurniawan, Andrie (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2021)
Abstract; This study explains the influence and relationship of discipline and creative promotion in increasing the work motivation of PT Askrida Jakarta employees in maintaining the number of customers and expanding the range of products , while the research objective is to examine the effect and relationship between variables and their correlation values ​​with quantitative research methods and the number of respondents as much 100 employees in a period of six months, from January to June 2019, and the results of the study showed that between variables showed positive and significant values, also for statistical tests explained the results were quite good so it needed to increase work motivation by continuing to improve discipline and promote creative in PT Asuransi Bangun Askrida Jakarta in order to increase company profits while maintaining employee welfare and maintaining customer satisfaction Keywords: discipline, creative promotion, motivation.